Evaluating meaningful levels of financial toxicity in gynecologic cancers. Issue 6 (June 2021) - Esselen, Katharine McKinley; Gompers, Annika; Hacker, Michele R; Bouberhan, Sara; Shea, Meghan; Summerlin, Sarah S; Rucker, Lindsay R; Huh, Warner K; Pisu, Maria; Liang, Margaret I
ABSTRACT : Objective : The Comprehensive Score for Financial Toxicity (COST) is a validated instrument measuring the economic burden experienced by patients with cancer. We evaluated the frequency of financial toxicity at different COST levels and stratified risk factors and associations with cost‐coping strategies by financial toxicity severity. Methods : We analyzed previously collected survey data of gynecologic oncology patients from two tertiary care institutions. Both surveys included the COST tool and questions assessing economic and behavioral cost‐coping strategies. We adapted a proposed grading scale to define three groups: no/mild, moderate, and severe financial toxicity and used χ 2, Fisher's exact test, and Wilcoxon rank sum test to compare groups. We used Poisson regression to calculate crude and adjusted risk ratios for cost‐coping strategies, comparing patients with moderate or severe to no/mild financial toxicity. Results : Among 308 patients, 14.9% had severe, 32.1% had moderate, and 52.9% had no/mild financial toxicity. Younger age, non‐white race, lower education, unemployment, lower income, use of systemic therapy, and shorter time since diagnosis were associated with worse financial toxicity (all p<0.05). Respondents with moderate or severe financial toxicity were significantly more likely to use economic cost‐coping strategies such as changing spending habits (adjusted risk ratio (aRR) 2.7, 95% CI 1.8 to 4.0 moderate; aRR 3.6, 95% CI 2.4 to 5.4 severe) and borrowing money (aRR 5.5, 95% CI 1.8 to 16.5 moderate; aRR 12.7, 95% CI 4.3 to 37.1 severe). Those with severe financial toxicity also had a significantly higher risk of behavioral cost‐coping through medication non‐compliance (aRR 4.6, 95% CI 1.2 to 18.1). Conclusions : Among a geographically diverse cohort of gynecologic oncology patients, nearly half reported financial toxicity (COST <26), which was associated with economic cost‐coping strategies. In those 14.9% of patients reporting severe financial toxicity (COST <14) there was also an increased risk of medication non‐compliance, which may lead to worse health outcomes in this group.